Mucosal Delivery of Cannabidiol: Influence of Vehicles and Enhancers - Peera Tabboon; Thaned Pongjanyakul; Ekapol Limpongsa; Napaphak Jaipakdee (MDPI AG, 2022)
In this study, the mucosal permeation and deposition of cannabidiol (CBD) with neat and binary vehicles were investigated. Permeation experiments were performed using static diffusion cells coupled with fresh porcine esophageal mucosa. The CBD-vehicle solutions were applied at a fixed dose (~5 mg/cm2), and the corresponding permeation parameters were calculated. In neat vehicles, the permeation flux (Jss) ranged from 0.89 ± 0.15 to 179.81 ± 23.46 µg·cm−2·h−1, while the CBD deposition ranged from 11.5 ± 1.8 to 538.3 ± 105.3 μg·cm−2. Propylene glycol (PG) and diethylene glycol monoethyl ether (DEGEE) yielded the highest permeability (Ps) and CBD deposition, while medium-chain triglycerides (MCT) yielded the lowest Ps and deposition. This was due to the difference in apparent partition coefficient (K), which is related to the solubility of CBD in the vehicle. The PG:DEGEE binary vehicle boosted Jss (1.5-1.6 fold) and deposition (2.0-2.7 folds) significantly, compared to neat DEGEE. The combination of DEGEE with MCT dramatically enhanced Jss (11-44 fold) and deposition (1.6-4.7 fold). The addition of lipophilic enhancers, laurocapram, and oleic acid, to PG:DEGEE and DEGEE:MCT vehicles significantly reduced Jss (0.3-0.7 fold) and deposition (0.4-0.8 fold) while nerolidol had no effect. These permeation reductions were found to be related to modification of the K and/or diffusivity values. This study provides useful basic information for the development of CBD formulations intended for transmucosal delivery.